From KKMB to IKM Southeast Sulawesi: The Organizational History of the Minangkabau Migrant Community in Kendari (1980–2024) - Fauziatul Hasana; Ahmadin; Rasyid Ridha (Ilomata International Journal of Social Science, 2026)
This article analyzes the historical dynamics and institutional transformation of Minangkabau migrant organizations in Kendari City, focusing on the transition from the Minangkabau Family Harmony (KKMB) established in the 1980s to the Southeast Sulawesi Minangkabau Family Association (IKM) in 2024. The study aims to examine how this organizational transformation reflects adaptive strategies in maintaining social cohesion and cultural continuity among the Minangkabau diaspora within a multicultural urban context in Eastern Indonesia. Employing a qualitative design grounded in historical methods and case study approaches, data were collected through in-depth interviews with organizational leaders and members, participant observation of organizational activities, and document analysis, including statutes (AD/ART), archival records, and administrative reports. The analysis is guided by the social capital framework of Robert Putnam, with particular emphasis on the operational dimensions of bonding and bridging social capital, trust, reciprocity, and social networks. The findings indicate that the transformation from KKMB to IKM represents not merely an administrative restructuring but a strategic institutional adaptation that reinforces internal solidarity (bonding) while simultaneously expanding external integration (bridging) with the local Southeast Sulawesi community. Empirically, the Kendari case both confirms and extends Putnam’s framework by demonstrating that diaspora organizations in plural urban settings actively negotiate identity and inclusivity, thereby complicating the dichotomy between bonding and bridging social capital through hybridized organizational practices.